SENGKETA TANAH KAWASAN HUTAN DAN RESOLUSINYA DALAM PERSPEKTIF FIQH - Abu Rokhmad (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
Land dispute on forest area in Blora Regency is still developing. This is a form of resistence among Blora community toward the patterns of forrest management by Perhutani since New Order. Many things became the trigger like illegal logging, violence involving community members, and claim on land ownership. This article studied the phenomenon applying fiqh perspective in order to develop peace building that was based on common good. However natural resources management constituted an important part in doing worship to God, so it needed to be accorded to Islamic spirit.